Mental health symptoms predict competency to stand trial and competency restoration success - Gay, Jeremy G. (Legal and criminological psychology, 2017)
Purpose. Although several studies have examined demographic and clinical variables associated with findings of incompetency to stand trial (IST), few studies have examined factors influencing competency restoration success. This study is among the first to longitudinally examine demographic variables and mental health symptoms’ impact on both IST and competency non-restoration. This study fills a gap in the competency to stand trial literature by utilizing the same defendants to examine progression through initial competency decisions to their eventual restoration outcomes. Methods. This study examined demographic variables and mental health symptoms differentiating defendants deemed competent to stand trial, not competent and restored, and not competent and not restored. We coded and analysed 237 competency evaluations consecutively conducted over a 3-year period. Results. Specific psychotic (e.g., thought derailment, delusions, auditory/visual hallucinations) and neuropsychological symptoms (e.g., impaired executive functioning, impaired mental status) were independently associated with findings of IST and non-restoration. Additional analyses revealed an intellectual disability diagnosis and a greater number of psychotic and manic symptoms predicted a decreased likelihood of competency restoration. Conclusions. These findings suggest more severe symptom combinations (e.g., psychotic and manic symptoms) are predictors of both initial findings of incompetency and non-restorability.